Aplikasi Zeolit-Y Berbahan Dasar Lempung Sidrap dan Abu Sekam Padi Sebagai Adsorpsi Logam Tembaga (Cu) dan Timbal (Pb) - Armayani Armayani; Damis Damis; Hasrianti Hasrianti; Angga Nugraha; Subaer Subaer (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2022)
This research examines zeolite-Y made from sidrap clay and rice husk ash as the adsorption of copper (Cu) and lead (Pb) metals. The method used is hydrothermal, using an autoclave with variations of Pb and Cu metals, namely 200, 400, and 600 ppm. The results showed that zeolite-Y was able to adsorb Cu and Pb well, as evidenced by the presence of Pb and Cu in the mapping results and EDS (Energy Dispersive X-Ray) and SEM (Scanning Electron Microscopy) showed the morphology of each sample of Cu and Pb metals. Pores indicate the absorption of Cu and Pb metals in the zeolite. The results of AAS (Atomic Absorption Spectrophotometer) show that the greater the levels of Cu and Pb produced, the greater the absorbent level.